2010
DOI: 10.1007/s11483-010-9147-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lipase, Bile Salts, and Polysaccharides on Properties and Digestibility of Tuna Oil Multilayer Emulsions Stabilized by Lecithin–Chitosan

Abstract: The influence of lipase, bile salts, and polysaccharides (pectin and maltodextrin) on the properties and digestibility of lecithin/chitosan-stabilized tuna oil-in-water multilayer emulsions were studied when they were subjected to an in vitro digestion model. All emulsions became unstable to creaming after passing through the digestion model, as deduced from the formation of large visible brown clumps on the top of the emulsions. The release of free fatty acids and glucosamine from the emulsions suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 52 publications
(78 reference statements)
2
38
0
Order By: Relevance
“…Tweens) etc. [46,[53][54][55][56]. Sarkar et al [47] reported on the effect of BS on lactofferin-stabilised emulsion.…”
Section: Duodenal Digestionmentioning
confidence: 99%
“…Tweens) etc. [46,[53][54][55][56]. Sarkar et al [47] reported on the effect of BS on lactofferin-stabilised emulsion.…”
Section: Duodenal Digestionmentioning
confidence: 99%
“…A possible explanation of this phenomenon is that the interfacial composition of the lipid droplets changed after digestion leading to droplets that were more stable to aggregation. For example, it is known that the original emulsifier in an oil-in-water emulsion may be removed from the droplet surfaces either through enzymatic digestion or through displacement by other surfactant active substances, such as bile, phospholipids or enzymes (Chu et al, 2009;Klinkesorn & McClements, 2010;Mun et al, 2007;Singh, Ye, & Horne, 2009;Wickham et al, 1998).…”
Section: Confocal Microscopymentioning
confidence: 99%
“…For example, cationic chitosan can bind to the surface of anionic lipid droplets that are stabilized by bile salts and/or phospholipids and reduce lipase activity by preventing lipase from coming into contact with the emulsified lipid substrate [9]. The negatively charged lipase may have acted as a bridge between the positively charged chitosan-coated droplets, causing them to clump together, and the interaction of chitosan with lipase may have caused some charge neutralization of the lipid droplets [14]. …”
Section: Discussionmentioning
confidence: 99%